PENGARUH MINDFULNESS TERHADAP CAREGIVER BURDEN LANSIA DENGAN DEMENSIA DI PANTI WREDA - Heru Ginanjar Triyono; Meidiana Dwidiyanti; Rita Hadi Widyastuti (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Data obtained in November 2017 at the time of screening obtained data that there were 35 Caregiver experienced burden with mild to severe category, which consisted of 10 people had a mild burden, 23 moderate burden people and 1 person had a heavy burden. Then at the time of the interview stated that the caregiver felt exhausted because approximately 8 hours of caring for the elderly with dementia, Caregiver also often withstand emotions related to the behavior of elderly people who are difficult to regulate. The research method used in this study was